Kongens Fald mellem dekadence og vitalisme - Svendsen, Erik (Passage - Tidsskrift for litteratur og kritik, 2022)
This article explores the tension between decadence and vitalism in Johannes V. Jensen’s famous novel. The decadence is a well-known dimension in the novel but vitalism has been less studied. By seeing correspondences between works of Friedrich Nietzsche and the novel the article demonstrates that vitalism plays a central role in the novel’s critical approach to the main protagonist, Mikkel Thøgersen, and the King.